2018
DOI: 10.1002/jor.24069
|View full text |Cite
|
Sign up to set email alerts
|

LagLoc—a new surgical technique for locking plate systems

Abstract: Treatment of oblique and spiral fractures remains challenging. The aim of this study was to introduce and investigate the new LagLoc technique for locked plating with generation of interfragmentary compression, combining the advantages of lag screw and locking-head-screw techniques. Oblique fracture was simulated in artificial diaphyseal bones, assigned to three groups for plating with a seven-hole locking compression plate. Group I was plated with three locking screws in holes one, four, and seven. The centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(37 reference statements)
1
0
0
Order By: Relevance
“…20,21 This increased stability relative to double plate fixation is conducive to early initiation of functional recovery exercises, thus accelerating joint function restoration and improving prognosis. 22 The results of this study also showed that the fracture healing time of locking plate internal fixation group was significantly shorter than that of double plate internal fixation group, and the recovery of knee function was also better than that of double plate internal fixation group.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 50%
“…20,21 This increased stability relative to double plate fixation is conducive to early initiation of functional recovery exercises, thus accelerating joint function restoration and improving prognosis. 22 The results of this study also showed that the fracture healing time of locking plate internal fixation group was significantly shorter than that of double plate internal fixation group, and the recovery of knee function was also better than that of double plate internal fixation group.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 50%